(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Considering the fact that the UK construction industry faces a growing demand for sustainable practices, this research is conducted to explore the justification of the use cases of BIM and Lean in DfMA with identification of associated themes. Research by Martinez et al. (2013) and Li et al., (2019) highlights the inefficiencies in industry and the resultant impact on productivity and sustainability, necessitating the need for modern measures to address these challenges. DfMA offers a promising path towards sustainable construction, and this study delves into the combined effects of BIM and Lean within DfMA workflows. BIM’s collaborative design capabilities enable early identification and mitigation of sustainability concerns in construction. Lean principles, emphasising continuous improvement and waste reduction, complement DfMA’s focus on resource efficiency. The justification, among others was that the integration of BIM and Lean methodologies within the framework of DfMA for sustainable construction is a research area of profound importance. The construction industry, identified as a cornerstone of economic growth, not only directly contributes to a nation’s economic prosperity but also exerts indirect influences on the growth trajectories of other industries. Besides the exploration of the integration of BIM and Lean within the DfMA context is paramount for achieving a holistic understanding of their collective contributions to sustainable construction practices in the industry. Interestingly, the research examined how BIM can optimise DfMA components for minimal environmental impact during design and construction; and how Lean practices, integrated within a BIM-DfMA framework, can further enhance resource efficiency. This is achieved by reducing rework through improved planning, optimising on-site logistics, and promoting just-in-time deliveries. By exploring the strategic integration of BIM, Lean, and DfMA, this research can inform industry best practices and guide policy development towards a more sustainable future for the UK construction sector. One of the recommendations was that there is need to develop standardised guidelines and best practices for BIM, Lean, and DfMA integration to benefit all stakeholders.